The Influence Of Service Quality And Brand Image On Consumer Satisfaction At Mr. Diy Talang Jawa Lahat - Wardana, Aditia; Yulanda, Delvina; Kesuma, Darwin (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the effect of service quality and brand image on consumer satisfaction at Mr. DIY Talang Jawa Lahat. The variables in this study were service quality (X1), brand image (X2), and consumer satisfaction (Y). The data analysis methods used were instrument testing (reliability testing, validity testing), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination testing. The results of the study showed that (1) service quality has a significant partial effect on consumer satisfaction, as shown by the calculated t value > t table (5.205 > 2.005). (2) brand image has a significant partial effect on consumer satisfaction, as shown by the calculated t value > t table (2.177 > 2.005). (3) Service Quality and Brand Image have a significant simultaneous influence on Consumer Satisfaction, as seen from the calculated f-value > f-table (59.997 > 2.005), and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05).